Cytokines in inflammatory bowel disease - P. L. Beck; J. L. Wallace (Mediators of Inflammation)
Over the past decade, much has been learned regarding the role of various cytokines in the pathogenesis of inflammatory bowel disease. Several cytokine ‘knockout’ models in mice have been shown to develop colitis, while alterations in the production of various cytokines has been documented in human Crohn's disease and ulcerative colitis. In recent years, attempts have been made to treat these diseases through modulation of cytokine production or action. This review focuses on the cytokines that have been implicated in the pathogenesis of inflammatory bowel disease. The evidence for and against a role for particular cytokines in intestinal inflammation is reviewed, as is the experimental and clinical data suggesting that cytokines are rational targets for the development of new therapies.